2013
DOI: 10.1007/s12094-013-1124-z
|View full text |Cite
|
Sign up to set email alerts
|

Identification of putative target genes for amplification within 11q13.2 and 3q27.1 in esophageal squamous cell carcinoma

Abstract: Target gene identification of amplifications or homozygous deletions will help to reveal the mechanism of tumor formation and explore new therapy method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 25 publications
2
29
0
Order By: Relevance
“…The results showed that 8q24 was the main amplified region and Tribbles pseudokinase 1 (TRIB1) was one of the genes located in it. Amplification of 8q24 is a common chromosomal abnormality in CRC [ 6 ] and some other cancers including acute myeloid leukemia (AML) [ 7 , 8 ], prostate cancer [ 9 ], gastric cancer [ 10 ], malignant mesothelioma [ 11 ], esophageal carcinoma [ 12 ] and ovarian cancer [ 13 ]. These suggest that 8q24 is significantly associated with human cancers and this region may carry oncogenes related to tumorigenesis and/or progression.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that 8q24 was the main amplified region and Tribbles pseudokinase 1 (TRIB1) was one of the genes located in it. Amplification of 8q24 is a common chromosomal abnormality in CRC [ 6 ] and some other cancers including acute myeloid leukemia (AML) [ 7 , 8 ], prostate cancer [ 9 ], gastric cancer [ 10 ], malignant mesothelioma [ 11 ], esophageal carcinoma [ 12 ] and ovarian cancer [ 13 ]. These suggest that 8q24 is significantly associated with human cancers and this region may carry oncogenes related to tumorigenesis and/or progression.…”
Section: Introductionmentioning
confidence: 99%
“…An increase of ALG3 expression has been presented in multi-drug resistance (MDR) cell lines and peripheral blood mononuclear cells of MDR patients [6]. In steps with previous study, ALG3 expression was signi cantly up-regulated in esophageal squamous cell carcinoma, primarily in patients with lymph node metastasis [8]. Moreover, up-regulation of ALG3 was obviously related to cervical cancer [9].…”
Section: Introductionmentioning
confidence: 53%
“…By analyzing the TCGA database including 338 OSCC tumor and 32 normal tissues, ALG3 was picked up for further exploration. The data from TCGA presented that ALG3 was obviously enhanced in OSCC tumor tissues, which was consisted with the expression in esophageal squamous cell carcinoma and breast cancer [8,10] (Fig. 1A, p=4.735e-03).…”
Section: Alg3 Expression Was Associated With Overall Survival Of Osccmentioning
confidence: 90%
“…Among these, we found an overlap in the amplification frequencies of three different snoRNA/host gene couples, namely SNORA63/EIF4A2, SNORA63E/LINC00888, SNORD66/EIF4G1, in five different cancer types: HNSC, KIRC, SKCM, OV, and GBM. All these genes map to the same chromosomal location, 3q27, which also hosts different oncogenes (like TERT, PI3KCA, and BCL6) and has been shown to be frequently amplified in squamous cell carcinomas with different localizations (lung [44], esophagus [45], mouth [46]), in lymphomas [47], and in lung cancers different from LUSC (i.e., small cell lung carcinomas and adenocarcinomas [48]). Although it is difficult to speculate a possible mechanism for specific snoRNA/host gene CNA contribution to cancer onset, it is worthwhile to consider that the snoRNAs/host gene couples highlighted for being altered in multiple cancer types (Section 3.3) have already been recognized for having a specific biological relevance, which could be linked to clinical relevance in many cancer types (Table 2).…”
Section: Discussionmentioning
confidence: 99%